Neonatal Screening for Critical Congenital Heart Defects - Ewer, Andrew (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Critical congenital heart defects (CCHDs) are potentially life-threatening malformations that remain a significant cause of neonatal mortality and morbidity. Failure to diagnose these conditions shortly after birth may result in acute cardiovascular collapse and death. The identification of CCHDs by routine newborn clinical examination is routine in many countries, but consistently misses over a third of cases, and, although antenatal ultrasound screening can be very effective in early diagnosis, the provision and accuracy of ultrasound screening is highly variable. As most CCHDs present with mild cyanosis (hypoxaemia), which is frequently clinically undetectable, pulse oximetry is a rapid, simple, painless method of accurately identifying hypoxaemia, which has gained popularity as a screen for CCHD. This Special Issue of the International Journal of Neonatal Screening, devoted to ""Neonatal Screening for Critical Congenital Heart Defects (CCHDs)"", will consider the evidence for CCHD screening with pulse oximetry, the acceptability and cost-effectiveness of this intervention, the additional non-cardiac conditions which it may also identify, and international experiences of introducing CCHD screening across the globe.